The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/aji.12472
|View full text |Cite
|
Sign up to set email alerts
|

Secrets of Endometrial Receptivity: Some Are Hidden in Uterine Secretome

Abstract: Problem Endometrium, the innermost mucosal layer of the uterus, serves as a lodge for the embryo in eutherian mammals. The endometrium is constituted of various cell types, and each cell type executes specific functions to facilitate embryo implantation and development. It is well established that the endometrium, despite being non-permissive to the embryo for the major period of a menstrual cycle, is irreplaceable in the scheme of events essential for procreation. However, the embryo, before initiating physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 81 publications
1
31
0
Order By: Relevance
“…Additionally, cytokines, chemokines, proteases, antiproteases, growth factors present in the endometrial fluids or secretions have also been found to be important for the maintenance of microenvironment during implantation which helps in endometrium-embryo crosstalk. 30,32 Similarly, in our study, the genes involved in downregulation of immune and inflammatory response-related functions ( 1,8,23 Their downregulation in our study indicates similar results even in COS. 37 In the current study, lower expression of LIF and IL6ST in glandular epithelium and stromal cells was observed in cases compared to controls even on protein level by immunohistochemistry, indicating the significance of these genes in endometrial receptivity, and therefore validates the results by microarray and real time.…”
Section: Downregulated Genes In Immune Response Downregulated Genes Isupporting
confidence: 85%
“…Additionally, cytokines, chemokines, proteases, antiproteases, growth factors present in the endometrial fluids or secretions have also been found to be important for the maintenance of microenvironment during implantation which helps in endometrium-embryo crosstalk. 30,32 Similarly, in our study, the genes involved in downregulation of immune and inflammatory response-related functions ( 1,8,23 Their downregulation in our study indicates similar results even in COS. 37 In the current study, lower expression of LIF and IL6ST in glandular epithelium and stromal cells was observed in cases compared to controls even on protein level by immunohistochemistry, indicating the significance of these genes in endometrial receptivity, and therefore validates the results by microarray and real time.…”
Section: Downregulated Genes In Immune Response Downregulated Genes Isupporting
confidence: 85%
“…Furthermore, we detected the down-regulation in IF patients of genes involved in cell cycle and apoptosis regulation ( Supplementary Table 3 ), indicative of a reduced rate of cell proliferation in endometrium. Additionally, in this meta-analysis, the down-regulation genes in IF patients were also enriched in estradiol response, chemokines, growth factors, which have been found to be important for the maintenance of microenvironment during implantation supporting the endometrium-embryo crosstalk [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We used a comprehensive high-quality PPI database downloaded from the InnateDB [ 30 ], which participates in the International Molecular Exchange (IMEx) consortium [ 31 ]. The database was derived by manually curating protein interaction data from published literature and by integrating experimental data from several PPI databases including MINT [ 32 ], IntAct [ 33 ], BIND, BioGRID [ 34 ] and DIP [ 35 ]. The gene networks were visualized using Cytoscape 3.2.0 [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Endometrial alterations in clinical practice are characterized by the endometrial thickness and morphological alterations which require further histological [6] and biochemical investigations [7].…”
Section: Introductionmentioning
confidence: 99%